A Puzzling Protein from Variovorax paradoxus Has a PLP Fold Type IV Transaminase Structure and Binds PLP without Catalytic Lysine - Konstantin M. Boyko; Ilya O. Matyuta; Alena Y. Nikolaeva; Tatiana V. Rakitina; Vladimir O. Popov; Ekaterina Yu. Bezsudnova; Maria G. Khrenova (Crystals, 2022)
Effective biocatalysts for the synthesis of optically pure amines from keto precursors are highly required in organic synthesis. Transaminases are a large group of PLP-dependent enzymes, which can be utilized for production of chiral amines or amino acids. The bioinformatic approach previously made to search for promising transaminases with unusual characteristics surprisingly revealed mysterious genes in some Gram-negative bacteria, which products were annotated as aminotransferases, but they lacked the key catalytic lysine residue required for covalent binding of the PLP-cofactor. To address the question of which products these genes encode, we obtained the first structure of such a type of protein from the bacterium Variovorax paradoxus (VP5454) and provided its comprehensive analysis. We demonstrated that VP5454 has a typical aminotransferase fold and architecture of the active site, where substitution of the catalytic lysine with asparagine was observed. Despite that no covalent adduct can be formed between PLP and asparagine residue, using X-ray analysis and molecular dynamic (MD) simulation, we demonstrated that VP5454 is able to bind the PLP molecule in the transaminase in a specific manner, with PLP coordinated via its phosphate moiety. Taking into account a number of sequences homologous to VP5454 with a substituted catalytic lysine found in the genomes of various bacteria, we speculate that the proteins encoded by these sequences may have hidden functional roles.